ANALISIS DISTRIBUSI ARAH DAN KECEPATAN ANGIN UNTUK DETEKSI CROSSWIND DI BANDARA RADIN INTEN II MENGGUNAKAN METODE WINDROSE - Amidayantik, Damil; Triloka, Joko; Mutiara, Suci (Institut Informatika Dan Bisnis Darmajaya, 2025)
Aviation safety is strongly influenced by wind direction and wind speed, particularly during critical phases of flight such as take-off and landing. One of the most challenging wind conditions for airport operations is crosswind, which occurs when the wind blows perpendicular to the runway direction and can reduce aircraft controllability. Therefore, a comprehensive understanding of wind characteristics around an airport is essential to support safe and efficient flight operations. This study analyzes the distribution of wind direction and wind speed at Radin Inten II Airport using the windrose method as the primary analytical approach, supported by histogram and heatmap visualizations. The dataset consists of historical wind observations collected hourly by the Meteorology, Climatology, and Geophysics Agency (BMKG) Lampung over a ten-year period from 2014 to 2023. The data were processed to identify dominant wind directions, wind speed variability, and periods with a higher potential for crosswind conditions that may disrupt airport operations. The results indicate that the dominant wind direction at Radin Inten II Airport generally originates from the northwest, with prevailing wind speeds ranging between 2 and 6 knots, reflecting relatively stable wind conditions. However, several periods exhibit higher wind speeds that may increase the risk of crosswind occurrences. Further analysis reveals specific months with an increased frequency of crosswind events approaching critical operational thresholds, which require greater attention from airport operators. The findings of this study provide practical recommendations for airport management in determining appropriate runway usage, enhancing situational awareness during high-risk periods, and developing mitigation strategies such as flight schedule adjustments and runway infrastructure improvements. In addition, this research is expected to serve as a reference for other airports with similar wind characteristics in improving aviation safety and operational efficiency.